An Efficient Schema of a Special Permutation Inside of Each Pixel of an Image for its Encryption - Hana Ali-Pacha; Naima Hadj-Said; Adda Ali-Pacha; Mustafa Mamat; Mohamad Afendee Mohamed (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The developments of communications and digital transmissions have pushed the data encryption to grow quickly to protect the information, against any hacking or digital plagiarisms. Many encryption algorithms are available on the Internet, but it's still illegal to use a number of them. Therefore, the search for new the encryption algorithms is still current. In this work, we will provide a preprocessing of the securisation of the data, which will significantly enhance the crypto-systems. Firstly, we divide the pixel into two blocks of 4 bits, a left block that contains the most significant bit and another a right block which contains the least significant bits and to permute them mutually. Then make another permutation for each of group. This pretreatment is very effective, it is fast and is easy to implement and, only consumes little resource.